The impact of parent migration on education expenditures for children in rural China - Jannat, Semonti; Parsons, Ryan (Australian and International Journal of Rural Education, 2025)
More than 200 million residents of rural China migrate to urban destinations for work, but due to restrictions on household registration (the hukou system), these migrations are often cyclical and temporary. These patterns have resulted in a phenomenon in which rural children are left in the care of relatives while parents migrate for higher wages in urban labour markets. The impacts of this migration on children’s outcomes are often ambiguous: while separation from parents is associated with a range of developmental and social challenges, the higher incomes that come from urban labour markets allow parents to send substantial remittance payments back to their primary household. We use panel data from the China Family Panel Studies (2010–2014) to test how parental migration affects (1) household education expenditure and (2) saving for future education. Left behind children are poorer and experience smaller increases in education spending than peers with co-resident parents. At the same time, households with a migrating parent are modestly more likely to start saving for education. These results, robust to propensity score matching, suggest migration changes expectations more than near-term expenditures.